Advertising Language in Sinar Harian Newspaper - Sharil Nizam, Sha’ri; Mohd Hazreen Shah, Hasan; Nurul Fadzlin, Mohd Asr; Veeramohan, Veeraputhran; Muhammad Shafiq Firdaus, Mohd Rani; Abdul Hamid, Moiden; Azean Idruwani, Idrus; Zuraini, Seruji (Human Resource Management Academic Research Society, 2021)
This study is an observation of the use of language in advertising language. This writing involves a study of the form of content analysis on selected advertisements. This study gives the main focus on the aspect of interpreting the meaning of advertisements using a languageadjusted approach by Kamaruddin (1995). This theory emphasizes the importance of context in the interpretation of the use of the Malay language ads involving all aspects of the circumstance of users and usage conditions. This reason to achieve advertising goals, advertisers do not emphasize grammatical aspects when building ad scripts. Therefore, user confusion will arise on the adjustable meaning of ad language that often uses implicit elements. In the construction of a language, its use by members of the community must be the main goal. A language that has been developed will not be meaningful if it has not been fully used by the members of the community who developed it (Asmah, 1988).